2003
DOI: 10.1042/cs104024pa
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, Characteristics and Correlates of Undetected Coeliac Disease in England

Abstract: AIMS:The aim of this study was to investigate MlF expression and activity in human sporadic colorectal adenomas and in intestinal adenomas from the Apc mouse model of familial adenomatous polyposis. METHODS: lmmunohistochemistry was performed on archival formalin-fixed, paraffin-embedded human sporadic colorectal adenomas (n=56), and on small and large intestine of Apc mice and wild type littermates. Human MLF protein levels were analysed in fresh paired colorectal adenoma and normal mucosa samples by ELSA (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
73
2
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 0 publications
11
73
2
7
Order By: Relevance
“…The observation of fewer cases of breast cancer than expected, although not statistically significant, is of interest particularly in the light of similar observations in previous reports. 10,16 The reasons for this decrease could be related to the lower body weight of people with coeliac disease 17 or their lower rates of smoking. 18 In conclusion, in this large, prospective, populationbased cohort study we found no overall increase in the risk of incident malignancy in clinically diagnosed coeliac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of fewer cases of breast cancer than expected, although not statistically significant, is of interest particularly in the light of similar observations in previous reports. 10,16 The reasons for this decrease could be related to the lower body weight of people with coeliac disease 17 or their lower rates of smoking. 18 In conclusion, in this large, prospective, populationbased cohort study we found no overall increase in the risk of incident malignancy in clinically diagnosed coeliac disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Undiagnosed CD in older adults is not associated with an increase in mortality but is associated with impaired bone density and lower ferritin levels. Furthermore, a minority of subjects with undiagnosed CD, especially women, will eventually be clinically diagnosed with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Once thought to be rare, CD affects approximately 1% of the population [1][2][3] and appears to be associated with increased mortality [4][5][6] along with substantial morbidity, 7,8 much of which is preventable or reversible with the gluten free diet. 9,10 Well recognized are the gastrointestinal consequences of severe malabsorption with weight loss or growth failure, macro-and micronutrient deficiencies and a host of extra-gastrointestinal manifestations varying from autoimmune disorders to arthralgia to neurologic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los países europeos la positividad de autoanticuerpos se describe como de 0,3% a 2,4% de la población y es menos común en Alemania y más en Finlandia. (5)(6)(7). En São Paulo la prevalencia de la enfermedad celíaca es del 0,6%, la cual es similar a las tasas reportadas en Portugal e Italia (5,7,8).…”
Section: Introductionunclassified